Facial Wash Gel Formulation from Papaya Leaf Extract (Carica papaya L.) With Carbopol 940 As Gelling Agent and Its Stability Study - Akmal, Tubagus; Yenni Puspita Tanjung; Irma Indriani (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2024)
Abstract—Propionibacterium acnes is a bacterium that significantly contributes to the development and progression of acne—the phenomenon of bacterial proliferation. The alkaloid carpain present in papaya leaf extract exhibits antibacterial properties against Propionibacterium acnes, a bacterium associated with the development of acne. The facial wash is a cleansing product that removes bacteria and debris from the skin. This study aims to develop a facial wash gel formulation employing papaya leaf extract to treat and inhibit acne-causing bacteria. The formulation will involve the use of different concentrations of Carbopol 940 polymer, namely FI (1%), FII (1.5%), and FIII (2%), as a gelling agent. The research conducted falls under the category of experimental research. The assessment of facial wash gel formulations encompasses various parameters, such as organoleptic evaluation, homogeneity analysis, pH determination, viscosity measurement, spreadability assessment, and foaming capacity examination. The study's findings indicate that the formulation of the FII facial wash gel successfully fulfils all criteria for preparation evaluation. FI fails to satisfy the criteria for spreadability testing, while FIII needs to fulfil the homogeneity and viscosity testing requirements. The viscosity test was significantly affected by different amounts of Carbopol 940, which was used as a gelling agent. The pH, spreadability, and foamability tests were not significantly affected (p>0.05). Keywords: acne, carbopol 940, carica papaya, facial wash gel Abstrak—Propionibacterium acnes merupakan bakteri yang sangat berperan dalam patogenesis timbulnya jerawat. Pertumbuhan bakteri. Di dalam ekstrak daun pepaya terkandung alkaloid karpain yang berfungsi sebagai antibakteri penyebab jerawat (Propionibacterium acnes). Facial wash menjadi salah satu produk yang dapat digunakan untuk membersihkan kulit dari bakteri dan kotoran yang menempel. Penelitian ini bertujuan untuk memformulasikan sediaan facial wash gel dari ekstrak daun pepaya untuk mengobati jerawat serta mencegah pertumbuhan bakteri penyebab jerawat dengan variasi konsentrasi polimer Carbopol 940 sebagai gelling agent yaitu FI (1%), FII (1,5%), dan FIII (2%). Jenis penelitian yang dilakukan adalah penelitian eksperimental. Evaluasi sediaan facial wash gel meliputi pengujian organoleptik, homogenitas, pH, viskositas, daya sebar, dan daya busa. Hasil dari penelitian menunjukkan formulasi sediaan facial wash gel FII memenuhi semua syarat evaluasi sediaan. FI tidak memenuhi syarat uji daya sebar, sedangkan pada FIII tidak memenuhi syarat uji homogenitas dan viskositas. Variasi konsentrasi Carbopol 940 sebagai gelling agent memberikan hasil berpengaruh secara signifikan (p<0,05) terhadap uji viskositas tetapi tidak berpengaruh secara signifikan (p>0,05) terhadap uji pH, daya sebar, dan daya busa. Kata kunci: daun papaya, gel sabun muka, jerawat, karbopol 940